Multilingualism, Teaching, and Learning Foreign Languages in Present-Day Hungary - JUDITH NAVRACSICS; CLAUDIA MOLNÁR (Indonesian Research Journal in Education |IRJE|, 2017)
Hungary is a monolingual state in Central Eastern Europe, where the Hungarian language, as the official language, is spoken by the whole population, including persons belonging to national and linguistic minorities. On the territory of Hungary, in the course of history, there have always lived representatives of other cultures and speakers of other languages. Nevertheless, in terms of the ability of speaking more than one language, within the European Union, Hungary is left behind, according to the latest Eurobarometer survey. In this paper we will highlight some of the facts and problems undermining real multilingualism in Hungary.